2020
DOI: 10.1093/cid/ciaa489
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Immunoglobulin G and IgM Antibodies Against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)

Abstract: We profiled the serological responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid (N) protein and spike (S) glycoprotein. The majority of the patients developed robust antibody responses between 17 and 23 days after illness onset. Delayed, but stronger, antibody responses were observed in critical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
318
2
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(356 citation statements)
references
References 9 publications
(10 reference statements)
20
318
2
10
Order By: Relevance
“…Supporting this are other studies that report overall low IgM responses to SARS-CoV-2 that are often preceded by IgG. 14,17 These data highlight the benefit of measuring all three anti-SARS-CoV-2 antibody isotypes to maximize sensitivity. In the case of SARS-CoV-2, it is unknown for how long IgM, IgA, or IgG antibodies remain detectable after infection.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Supporting this are other studies that report overall low IgM responses to SARS-CoV-2 that are often preceded by IgG. 14,17 These data highlight the benefit of measuring all three anti-SARS-CoV-2 antibody isotypes to maximize sensitivity. In the case of SARS-CoV-2, it is unknown for how long IgM, IgA, or IgG antibodies remain detectable after infection.…”
Section: Discussionmentioning
confidence: 52%
“…Nonetheless, other publications indicate that the time courses are comparable. 14,17,22 Our serological studies measured antibodies to the RBD of SARS-CoV-2. We chose this viral antigen because of its specificity to SARS-CoV-2, and because anti-RBD antibodies are typically neutralizing.…”
Section: Negative Results Do Not Completely Preclude Sars-cov-2mentioning
confidence: 99%
“…IgG detection may improve and speed up the diagnosis of COVID-19 in symptomatic patients, particularly in negative SARS-CoV-2 PCR cases. It has been shown that in up to 15% of COVID-19-positive patients IgG antibodies are detectable during the rst week following the onset of symptoms [8], although reaching 100% of the patients required two additional weeks [8,12,13,20]. Here, we examined the performance of serology as an adjuvant for the diagnosis of COVID-19 using commercially available procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This potentially allows to improve the microbiological diagnosis along with RNA detection from nasopharyngeal swabs in active cases and also detect past/cured cases [8]. The serological detection of IgG against SARS-CoV-2, mostly using inhouse procedures, has shown a sensitivity that ranges between 78% and 100% in patients requiring hospital admission [7][8][9][10][11][12][13][14][15]. Abbott´s SARS-CoV-2 IgG assay is a recent commercial chemiluminescence immunoassay (CLIA) platform approved by the FDA that allow detecting IgG in serum samples and has been validated in samples from hospitalized patients with COVID-19 [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a limitation of antibody tests is that they require a longer window period after infection than RT-PCR. Actually, the median IgM and IgG seroconversion period has been reported to be 10 days or longer after symptom onset [4][5][6] . However, information on the early time courses of serum antibody titers and the sensitivity and speci city of antibody tests after the onset of COVID-19 symptoms could make these tests more useful for the COVID-19.…”
Section: Introductionmentioning
confidence: 99%